Using press materials in learning French language - Saidova , Zarina (The Lingua Spectrum, 2025)
This article is devoted to the topic of “Using Press Materials in Learning French language” and analyzes the importance of press materials in learning French, the methods of using them and their effectiveness. Through the use of press materials, various articles, podcasts and magazines, it was studied how and why foreign languages ​​should be given importance.In addition, the possibilities and convenience of authentic materials are emphasized.